Simulasi Wisata dalam Reels Instagram bagi Mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
Traveling during the COVID-19 pandemic cannot be done due to restrictions on activities outside the house, this gives rise to reels with niche of traveling on instagram increasingly in demand by the public to treat the desire for physical vacation. This research conducts to find out, explain, and analyze the reasons and impacts of watching tourism simulations in traveling reels on instagram for FISIP Unud students. This research uses a descriptive qualitative approach and simulation theory from Jean Baudrillard. Simulation is a blur against the boundaries of the real and virtual worlds. The reason FISIP Unud students watch traveling reels are to get information about tourist attractions, the effects of travel bloggers, interesting spectacles, practical knowledge, and entertainment. Reels traveling in cyberspace can have impacts on the real world for FISIP Unud students. Traveling reels those give rise to simulations are the phenomenon of blurring the boundary between reality and sign. Reality represents one's traveling experience and a sign that represents traveling reels. The impacts of watching traveling reels is divided into positive impacts and negative impacts. Simulations-related analysis in traveling reels is also done to see whether or not the simulations run for FISIP Unud students. The positive impacts are to get entertainment, knowledge of tourist attractions increases, and practical knowledge. While the negative impacts, time wasting behavior and ignoring important activities that should be done, can not distinguish real experiences with virtual experiences in a media, the emergence of a new cluster of COVID-19 spread due to the massive number of visitors, consumptive behavior, damage to facilities and waste and imitating dangerous attractions. The existence of tourist simulations in instagram reels still has to be wary of the community, especially the negative impacts that arise.